THE LIBERAL ARTS IN ISLAMIC HIGHER EDUCATION: PROBLEM AND PROSPECT IN INDONESIA - Yusak, Nailil Muna (PEOPLE: International Journal of Social Sciences, 2015)
The growing number of Muslim elite in Indonesia who advocates violence and religious intolerance practices has left Indonesian policy on religious education in question. Islamic universities play a decisive role in educating Indonesian Muslim elites with many graduates who are Muslim thinkers of national and international standing. This paper aims to present an elaborative discussion on Islamic education practitioner’s viewpoint towards the Indonesian Liberal Studies Initiative task force’s proposal to further Indonesian Higher Education through the Liberal Arts. It will limit its focus on problem and prospects the liberal arts might bring to address the issue of religious illiteracy currently faced by Islamic universities in Indonesia. Through qualitative interview and observation at Syarif Hidayatullah State Islamic University, it is revealed that integration of knowledge and revitalizing the content of civics education subjects are key strategies to address the issue. An analysis of both the history of Liberal Arts education and interviews shows problem faced by Islamic higher education in responding to the task force’s proposal; politicization of language of liberalism and partial implementation of the integration of knowledge concept in the body of Islamic university in Indonesia.